Digital Farming and Smart Farming from the Perspective of Agricultural Students at Malikussaleh University 2022 - Kamaruddin Hasan; Masriadi; Muchlis; Asmaul Husna (Proceedings of Malikussaleh International Conference on Multidisciplinary Studies (MICoMS), 2022)
This study describes the views of agricultural students in seeing the opportunities and challenges of the era of digital farming and smart farming. To further grow their interest to be ready to become agricultural entrepreneurs who are creative, innovative, professional, competitive and able to absorb agricultural sector jobs. According to the Central Bureau of Statistics (BPS) national labor force survey, 20.62% of Indonesian youth work in the agricultural sector in August 2020, an increase compared to the previous period in 2019 which amounted to 18.43%, and will continue to increase until 2022. An increase in the number of young people in the sector agriculture can be a momentum to expand it. As many as 85.62% of them are internet users and have the opportunity to become early adopters of digital technology in the agricultural sector. So far, farmers' understanding of digital farming and smart farming is low because the majority of farmers have graduated from elementary and secondary schools. The average age is over 45 years, which makes it difficult to adapt to digital technology. Helplessness when dealing with digital media technology. The increasing number of young people interested in the agricultural sector is a hope as well as an opportunity to increase the development of a digital-based agricultural world. Of course this can be integrated into agricultural extension programs by millennials provided that agricultural students and alumni have adequate digital skills. That currently modernization of agriculture is a necessity. The agricultural sector continues to move towards digital farming and smart farming. Digitization of Agriculture facilitates monitoring, marketing, technology and helps accelerate the production process. Implementation of intelligent and critical use of digital media. The final results of this study are descriptive views and strategies of agricultural students regarding the phenomenon of digital farming and smart farming. Primary and secondary data were obtained through observation, interviews, Focus Group Discussion and literature review. Theoretical basis, concepts and models as well as scientific contributions are used by Digital Skills or Digital Literacy, Digital Farming, Smart Farming 4.0 and Agricultural Students. The research informants consisted of agricultural students and alumni, digital skills experts, agricultural academics and relevant stakeholders. Data analysis used snow ball informants and cross checks, synchronization, compression, reduction, data display and conclusion. The results of the study show that Malikussaleh University agricultural students and alumni as millennials are active internet users with various media that have the opportunity to become early adopters of digital technology in the agricultural sector towards Digital Farming and smart farming. Digitizing agriculture with the active involvement of millennials will facilitate monitoring, marketing, technology and help accelerate the production process by implementing the use of digital media intelligently and critically. The stigma of agriculture only for those with low education seems to still exist. Need to increase understanding of digital farming and smart farming among Millennials. Maximum implementation of digital farming and smart farming is a big hope in the hope of being able to realize a sustainable agricultural system.